Comparison of full-mouth and partial-mouth disinfection modalities in nonsurgical periodontal treatment for periodontitis: a randomized clinical trial in Vietnam - Nguyen, Thi Thuy Duong; Tran, Thi To Uyen (Tạp chí Y Dược Huế, 2023)
Background: Periodontitis is the most common form of periodontal disease, greatly affecting the aes - thetics, function as well as patient’s quality of life. In the periodontal disease treatment strategy, nonsurgical treatment is considered as the initial phase for anti-infection and soft-tissue management. Objective: This study aims to compare the effect of two nonsurgical periodontal modalities: one-stage full-mouth and par - tial-mouth protocols for periodontitis. Materials and Methods: 60 patients with chronic periodontitis were randomly allocated to 2 groups. Group I (n = 30) was treated according to partial-mouth therapy. Group II (n = 30) was treated according to full-mouth disinfection therapy. Periodontal parameters were assessed at baseline and 1, 3, and 6 months, including plaque index, gingival index, periodontal probing depth, clinical attachment loss, and bleeding on probing. Results: Both two treatment modalities resulted in significant improvements in all clinical parameters over the entire duration of the study (p < 0.05). Full-mouth disinfec- tion therapy showed significantly better improvements than the partial-mouth one during follow-up times (p < 0.05). Conclusion: Nonsurgical periodontal treatment has positive effects on controlling periodontitis. Full-mouth therapy shows clinical benefits over partial-mouth therapy in improving periodontal conditions.